Wittgenstein's critique of Russell's multiple relation theory of judgement - Connelly, James R. (London : Anthem Press, 2021)
This book sets out to adjudicate the scholarly controversy surrounding Wittgenstein's May-June 1913 critique of Russell's multiple-relation theory of judgement. It also aims to familiarize readers with the historical events, textual evidence, letters, working notes and diagrams which are crucial to a correct appreciation of Wittgenstein's criticisms.
Works by Other Authors -- Index
Includes bibliographical references (pages [195]-199) and index.
JSTOR
Keywords: Wittgenstein, Ludwig, -- 1889-1951.; Russell, Bertrand, -- 1872-1970.; Russell, Bertrand, -- 1872-1970; Wittgenstein, Ludwig, -- 1889-1951; Judgment; Judgment; Jugement; Logic; PHILOSOPHY; Language; Judgment; Electronic books